A textual analysis for the term ‘Wasatiyyah’ (Islamic moderation) in selected quranic verses and prophetic tradition - Yaakub, Muhamadul Bakir; Othman, Khatijah (Journal of Education and Social Science (JESOC), 2016)
The study of the term ‘Wasatiyyah’ has attracted the attention of many scholars in various fields such as linguistic, sociopsychologies, Islamic development and also in the area of religious contexts. In this regards, a similar term also exists in many other languages such as ‘moderation’ in English and ‘kesederhanaan’ in Malay. It can be considered as one of a humanistic conceptual thinking or understanding in a certain particular area or a system of thought within human communities. Therefore, a textual focus on a deeper understanding of the term ‘Wasatiyyah’ is crucial. Hence, this study is an exploratory study to identify the real meaning of the term ‘Wasatiyyah’ in its context and usage in agreement with the Quranic verses and Prophetic Tradition. This study adopted Systemic Functional Linguistics (SFL) theory as an analytical tool. SFL help to analyze the term ‘Wasatiyyah’ based on three broad functional principals of the language used. They are experiential (ideational), interpersonal and textual meanings. In order to understand the full functionality of any text, it is necessary to consider all of those three meanings simultaneously. Thus, to achieve a comprehensive textual analysis of the term ‘Wasatiyyah’, this study used selected sample texts taken from the glorious Quran and the Prophetic traditions. The main findings pointed out that SFL analytical tool can be applied to differentiate various social aspects of language use such as religious, political, economic and so on within the texts. Such an analysis of texts may lead to providing some explanations and solutions of the social and cultural problems in which human beings may face in everyday life.